2010
DOI: 10.4067/s0717-97072010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering: Metal Nanostructures Coated With Langmuir-Blodgett Films

Abstract: on leave from the department of chem. and biochem, university of windsor, windsor, ontario, canada. (Received: August 30, 2010 -Accepted: November 16, 2010) aBStract This review deals with surface-enhancved Raman scattering (SERS) employing Langmuir-Blodgett (LB) films, which serve as model systems for developing theoretical and experimental studies to elucidate the SERS effect. In addition, LB films have be used as integral parts of molecular architectures for SERS-active substrates. On the other hand, SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…This is due to the presence of AgNPs in some points of the film, which gives rise to the phenomenon of surface-enhanced Raman scattering, or in this case surface-enhanced resonant Raman scattering (SERRS). This phenomenon can enhance the Raman signal up to 10 10 times in specific cases and commonly amplifications of 10 3 can be easily found [32]. RRS spectrum of FeTsPc can be observed over the course of the entire mapped area ( Fig.…”
Section: Lbl Film Morphologymentioning
confidence: 91%
“…This is due to the presence of AgNPs in some points of the film, which gives rise to the phenomenon of surface-enhanced Raman scattering, or in this case surface-enhanced resonant Raman scattering (SERRS). This phenomenon can enhance the Raman signal up to 10 10 times in specific cases and commonly amplifications of 10 3 can be easily found [32]. RRS spectrum of FeTsPc can be observed over the course of the entire mapped area ( Fig.…”
Section: Lbl Film Morphologymentioning
confidence: 91%
“…Therefore, the use of PVP seems to be a good solution in SERS studies because this polymer gives relatively weak spectra, which was also observed by other researchers. 46,47 Of course, the presence of PVP on the Ag surface can interfere with "SERS analysis of traces of organic compounds", but this is a general problem in this type of measurement. The synthesis of cubic nanoparticles is not possible without the use of any surfactant that would not generate any SERS spectrum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since the pioneering work of Aroca et al , the Langmuir–Blodgett (LB) technique has been successfully utilized to record the SERS spectra of texas red, perylene, methacrylate, phthalocyanine, xanthene derivatives adsorbed on island films and silver‐coated tin spherical surface . In these reports, the LB films have been used as integral parts of molecular architectures for SERS active substrates.…”
Section: Introductionmentioning
confidence: 99%